Uromodulin in a Pathway Between Decreased Renal Urate Excretion and Albuminuria - Krajcoviechova, Alena; Marois-Blanchet, Francois-Christophe; Troyanov, Stephan; Harvey, Francois; Dumas, Pierre; Tremblay, Johanne; Cifkova, Renata; Awadalla, Philip; Madore, Francois; Hamet, Pavel (American journal of hypertension, 2019)
BACKGROUND: The mechanism explaining the inverse association between renal urate and albumin excretion remains unclear. First, we evaluated the impact of candidate variants in the main urate transporter genes (i.e., SLC2A9, SLC22A12, ABCG2) on the association between fractional excretion of uric acid (FEUA) and urinary albumin/creatinine ratio (uACR). Second, we examined uromodulin and sodium excretion as mediators of the association between FEUA and uACR. METHODS: We performed cross-sectional analysis of 737 French Canadians from the CARTaGENE cohort, a random sample of the Quebec population aged 40-69 years (a total of 20,004 individuals). Individuals with available genotyping and urinary data were obtained from a sub-study including gender-matched pairs with high and low Framingham Risk Score and vascular rigidity index. We further excluded individuals with an estimated glomerular filtration rate <60 ml/min/1.73 m2, glycosuria, and use of confounding medication. A spot urine sample was analyzed. Genotyping was performed using the Illumina Omni2.5-8 BeadChips. Genetic variants were analyzed using an additive model. RESULTS: Final analyses included 593 individuals (45.5% of men; mean age 54.3 ± 8.6). We observed an antagonistic interaction between rs13129697 variant of the SLC2A9 gene and FEUA tertiles on uACR (P = 0.002). Using the mediation analysis, uromodulin explained 32%, fractional excretion of sodium (FENa) 44%, and uromodulin together with FENa explained 70% of the inverse relationship between FEUA and uACR. Bootstrapping process confirmed the role of both mediators. CONCLUSIONS: Our data suggest that the association of albuminuria with decreased renal urate excretion may be modified by the transporter SLC2A9, and mediated by uromodulin and sodium handling.
Keywords: uric acid; mediation analysis; Uric Acid; Humans; lidé středního věku; Glomerular Filtration Rate; Female; Aged; renal solute excretion; dospělí; Uromodulin; Albuminuria; senioři; lidé; kyselina močová; Biomarkers; Genotype; hypertension; hodnoty glomerulární filtrace; albumin/creatinine ratio; proteiny usnadňující transport glukosy; SLC2A9 gene; albuminurie; Adult; Glucose Transport Proteins, Facilitative; biologické markery; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Renal Elimination; Cross-Sectional Studies; uromodulin; vyšetření funkce ledvin; genotyp; retrospektivní studie; blood pressure; sodium; mužské pohlaví; průřezové studie; eliminace ledvinami; urate transporter; Kidney Function Tests